Combination of drugs and carriers in drug delivery technology and its development - Du Y; Chen B (Dove Medical Press, 2019)
Ying Du, Baoan ChenDepartment of Hematology and Oncology, Zhongda Hospital, School of Medicine, Southeast University, Nanjing, People’s Republic of ChinaAbstract: The development of drug-loading technology will bring new and rapid development to the treatment of diseases. At present, drug delivery by nanoparticles, erythrocyte, and platelet have been studied extensively. Compared with traditional anticancer drugs, nano-drugs have shown many obvious advantages, disease treatment based on nanotechnology will bring a revolution in cancer treatment. Due to its inherent biocompatibility, large drug load and long half-life in the blood circulation, erythrocyte-inspired antibiotics, and some anticancer drugs delivery systems have also entered the clinical trial stage. At present, there are relatively few studies on drug delivery by platelets as carriers. It is necessary to overcome the shortcomings of platelets, such as easy activation, deformation, thrombosis, and difficult preservation. There are many ways to combine drugs with these carriers, and each has its own advantages and disadvantages. It is necessary to seek the best combination scheme to increase drug loading and reduce the damage to therapeutic components to the carriers, so as to bring more mature and reliable methods for the clinical application of drug delivery technology. Several drug-loading technologies and their development were described according to various categories. The combination of drugs and carriers is summarized for better understanding of its practical application.Keywords: drug delivery technology, carrier, combination, tumor